Increasing Thermal Stability of Gelatin by UV-Induced Cross-Linking with Glucose - Evan M. Masutani; Christopher K. Kinoshita; Travis T. Tanaka; Andrew K. D. Ellison; Brandon A. Yoza (International Journal of Biomaterials)
The effects of ultraviolet (254 nm) radiation on a hydrated gelatin-glucose matrix were investigated for the development of a physiologically thermostable substrate for potential use in cell scaffold production. Experiments conducted with a differential scanning calorimeter indicate that ultraviolet irradiation of gelatin-glucose hydrogels dramatically increases thermal stability such that no melting is observed at temperatures of at least 90°C. The addition of glucose significantly increases the yield of cross-linked product, suggesting that glucose has a role in cross-link formation. Comparisons of lyophilized samples using scanning electron microscopy show that irradiated materials have visibly different densities.